Evaluation of Non-HIV-Related, Drug-Sensitive Cluster Outbreaks of Tuberculosis with PCR-based DNA Fingerprinting - JM FitzGerald; WA Black; D Kunimoto (Canadian Respiratory Journal)
OBJECTIVES: To characterize two cluster outbreaks of tuberculosis by DNA fingerprinting and to evaluate the possibility of their association with human immunodeficiency virus (HIV) infection and multiple drug-resistant Mycobacterium tuberculosis.